Education Financial Management during Covid-19 Pandemic of Islamic Universities in South Kalimantan - Riinawati, Riinawati (IAIN Samarinda, 2021)
The purpose of this study was to determine the management of education financing in Islamic Universities in South Kalimantan. This research is in the form of descriptive qualitative with a library research data collection approach. The focus of this research will be to observe how the management of education financing in Islamic Universities throughout South Kalimantan, which consists of 13 educational institutions, both public and private categories. The results of this research show that the Covid-19 pandemic cannot be denied, causing the dropout rate to soar, due to the inability of students to pay their tuition fees. However, several campuses in South Kalimantan provide a policy of cutting payments and delaying payments so that students can continue to carry out the education process well. The financial management of Islamic higher education institutions in South Kalimantan during the Covid-19 pandemic has been carried out as effectively as possible. This is to maintain accountability and transparency to get good grades before getting cross-subsidy funds from the Government. The conclusions of this study are: the impact of Covid-19 has a very significant effect on education financing at Private Islamic Colleges in South Kalimantan but not at State Islamic campuses and the management of education financing amid the Covid-19 pandemic should be carried out very strictly.